Biomass and composition of understory vegetation and the forest floor carbon stock across Siberian larch and mountain birch chronosequences in Iceland - D. Sigurdsson, Bjarni; Magnusson, Borgthor; Elmarsdottir, Asrun; Bjarnadottir, Brynhildur (HAL CCSD, 2005)
International audience Changes in understory biomass, forest floor carbon (C) stock and vegetation composition were studied in six age-classes of Siberian larch (Larix sibirica) and two age-classes of native birch (Betula pubescens) in Iceland. The ground vegetation was less in the larch during the thicket stage and in the old-growth birch compared to a treeless pasture. Understory biomass was strongly related to canopy gap fraction across forest stands (P < 0.001), but not to soil pH or soil C/N ratio. Increased mass of dead wood and alterations in vegetation composition increased the forest floor C-stock of older forests. The forest floor had reached as high C-stock as the pasture's ground vegetation in ca. 50 years in the managed larch plantations and in ca. hundred years in the unmanaged birch forest. This study clearly shows the importance of which time-step is used when changes in forest floor C-stocks are computed for afforestation areas. Biomasse et composition de la végétation de sous-bois, et stock de carbone du sol dans une chronoséquence de mélèze de Sibérie et de bouleau pubescent en Islande. Nous avons étudié en Islande les modifications de biomasse, de composition floristique, et de stock de carbone en sous bois dans des peuplements de mélèze de Sibérie correspondant à 6 classes d'âge, et dans des peuplements de bouleau pubescent correspondant à deux classes d'âge. En comparaison avec une pâture non boisée, la végétation au sol était moins développée dans le peuplement de mélèze au stade gaulis et dans celui de bouleau mature. La biomasse au sol était fortement corrélée à la fraction de trouées dans l'ensemble des peuplements (p < 0,001) mais ni au pH du sol ou au rapport C/N. Une quantité croissante de bois mort et des changements dans la composition floristique étaient à l'origine de la croissance des stocks de carbone au sol dans les peuplement âgés. La surface du sol était aussi riche en carbone que la végétation d'une pâture dès l'âge de 50 ans dans les plantations gérées de mélèze ...